Fresh meat baits are currently the only available effective option to detect low‐density Vespula germanica (Hymenoptera: Vespidae) populations in South Africa. Issue 4 (23rd April 2019) - Haupt, Karla; Addison, Pia; Veldtman, Ruan
Abstract: The eusocial wasp Vespula germanica is a problematic invasive species in the Southern Hemisphere regions. Especially in New Zealand, Tasmania and Argentina, population densities can be very high and result in large negative impacts. In these regions, the development of baits is used not only to monitor population sizes but also to poison wasps when they return with treated baits to their nests. In contrast, this wasp has been present in South Africa since 1974 but is still confined to a small geographical area. Therefore, detection of the presence of V. germanica with a low level of false negatives is important. The foundation of such a monitoring strategy is a reliable bait or lure that can be placed, in a standard way, in different environments to detect wasp presence. In this study, we tested two baits and two lures at eight localities in 2013 and two baits and four lures at nine localities in 2014. Trap catches confirm low population densities of the target species even in the core of its distribution in South Africa with on average between 3 and 11 wasps (median of 0) caught per trap. Confirming classical bait preference studies, meat baits, specifically lean smoked ham and lean beef mince, trapped significantly more foragers in both sampling years than the unbaited control treatments. However, all catches using synthetic lures with various compounds known to be attractive to Vespula species were almost always indistinguishable from control treatments. Consequently, more research is required in optimising baiting of V. germanica in South Africa, where it occurs at relatively low densities and worker activity peaks when seasonal conditions are unfavourable (hot and dry). Low population densities could explain why synthetic lures that are effective in other invaded continents were not effective in South Africa.